Analysis of the Application of the Principles of Business Ethics in Islam - Jonathan, Bouyea; Joshua, Wang; Niva, Matteson (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
The development of technology has changed the way people conduct online buying and selling transactions, because it is more efficient, can be done anywhere. However, this raises new problems such as opportunities for fraud, payment, delivery of goods that are not suitable, guarantees that do not guarantee, which result in losses between the two parties. The purpose of this research is to understand in depth about the sales ethics of the lazadaa application. This type of research is field research with a descriptive qualitative approach. The results of the study that with the application of Islamic ethics in buying and selling, a healthy and blessed business climate will be achieved so that an Islamic community order is achieved in the lazadaa application. The conclusion of this study is that the sales ethics applied by sellers who are applied in the lazadaa application have gone well but some have not been in accordance with the principles of Islamic business ethics, by applying the ethics of buying and selling in accordance with the principles of sharia business ethics, it will achieve benefits in life both individually, society, and the state. The limitation in this study is that researchers only get a little information on lazadaa users. The author hopes that more attention will be paid to the principles of Islamic business ethics in using the lazadaa application to achieve a goal, hopefully it can be a lesson for all Muslims, so that there is an urge to make a good change.